2010
DOI: 10.1088/1674-1056/19/8/080503
|View full text |Cite
|
Sign up to set email alerts
|

Simulation study of the effects of time delay on the correlation function of a bistable system with correlated noises

Abstract: The effects of time delay on the fluctuation properties of a bistable system are investigated by simulating its normalised correlation function C(s). Three cases including linear delay, cubic delay and global delay in the system are considered respectively. The simulation results indicate that the linear delay enhances the fluctuation of the system (reduces the stability of the system) while the cubic delay and global delay weaken it (enforce the stability of the system), and the effect of cubic delay is more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…global delayed feedback), on the rate processes of a stochastic bistable system has also been investigated by a small delay expansion [36]. More recently, the effects of linear delay, cubic delay and global delay on the fluctuation properties of a bistable system have been studied by the stochastic simulation method [37]. In our previous studies, we investigated the effect of time delay on the NES effect in a metastable system, and it was found that the increase of the delay time can enhance or weaken the NES effect [38]- [40].…”
Section: Introductionmentioning
confidence: 99%
“…global delayed feedback), on the rate processes of a stochastic bistable system has also been investigated by a small delay expansion [36]. More recently, the effects of linear delay, cubic delay and global delay on the fluctuation properties of a bistable system have been studied by the stochastic simulation method [37]. In our previous studies, we investigated the effect of time delay on the NES effect in a metastable system, and it was found that the increase of the delay time can enhance or weaken the NES effect [38]- [40].…”
Section: Introductionmentioning
confidence: 99%